2018
DOI: 10.1097/htr.0000000000000371
|View full text |Cite
|
Sign up to set email alerts
|

Missing Voices: Profile, Extent, and 12-Month Outcomes of Nonfatal Traumatic Brain Injury in Aboriginal and Non-Aboriginal Adults in Western Australia Using Linked Administrative Records

Abstract: These findings suggest an urgent need for multisectoral primary prevention of TBI, as well as culturally secure and logistically appropriate medical and rehabilitation service delivery models to optimize outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…Australian studies indicate that assault plays a more prominent role in TBI rates for Indigenous Australians. A Western Australian study of person-linked hospital and mortality data (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) has found assault to be the mechanism of injury in over half (57%) of Indigenous Australian TBI hospital admissions (Katzenellenbogen et al, 2018); in contrast, only one in five (20%) non-Indigenous patient admissions were due to assault (Katzenellenbogen et al, 2018). Indigenous Australian women contributed to over 40% of these TBI admissions, double the proportion of their non-Indigenous counterparts (20.7%) (Katzenellenbogen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Australian studies indicate that assault plays a more prominent role in TBI rates for Indigenous Australians. A Western Australian study of person-linked hospital and mortality data (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) has found assault to be the mechanism of injury in over half (57%) of Indigenous Australian TBI hospital admissions (Katzenellenbogen et al, 2018); in contrast, only one in five (20%) non-Indigenous patient admissions were due to assault (Katzenellenbogen et al, 2018). Indigenous Australian women contributed to over 40% of these TBI admissions, double the proportion of their non-Indigenous counterparts (20.7%) (Katzenellenbogen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A Western Australian study of person-linked hospital and mortality data (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) has found assault to be the mechanism of injury in over half (57%) of Indigenous Australian TBI hospital admissions (Katzenellenbogen et al, 2018); in contrast, only one in five (20%) non-Indigenous patient admissions were due to assault (Katzenellenbogen et al, 2018). Indigenous Australian women contributed to over 40% of these TBI admissions, double the proportion of their non-Indigenous counterparts (20.7%) (Katzenellenbogen et al, 2018). These data reinforce findings from an earlier study which found that the rate of head injury-related hospitalisation for Indigenous people was 21 times higher than their non-Indigenous counterparts, and head injury due to assault for Indigenous women was 69 times the rate for non-Indigenous women (Jamieson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found there was higher likelihood of Aboriginal brain injury survivors living in non-metropolitan areas (82.5% vs. 51.5%). Katzenellenbogen et al (2018) reported that 56.4% of Aboriginal people in the study came from either remote or very remote areas as defined by the Accessibility/Remoteness Index of Australia-Plus (Australian Institute of Health and Welfare, 2004) as opposed to 10.6% of non-Aboriginal survivors. There was also a higher proportion of Aboriginal females (41.5% vs. 25.6%), a higher proportion of repeat injuries in Aboriginal survivors (23% vs. 7.4%), substantially higher assault-related TBI (57.4% vs. 19.6%) and higher levels of comorbidities.…”
mentioning
confidence: 99%
“…& Marshall, 1999;Rutland-Brown, Wallace, Faul & Langlois, 2005), the US (Linton, 2015;Rutland-Brown et al, 2005), New Zealand (Feigin et al, 2013) and Australia (Jamieson, Harrison & Berry, 2008;Katzenellenbogen et al, 2018). In the Australian context, epidemiological data from Western Australia (WA) (Katzenellenbogen et al, 2018) demonstrate differences between Aboriginal and non-Aboriginal TBI populations which have implications for service delivery. The study found there was higher likelihood of Aboriginal brain injury survivors living in non-metropolitan areas (82.5% vs. 51.5%).…”
mentioning
confidence: 99%